Cobalt Thiocyanate as Chromogenic Reagent for Determination of Trandolapril and Aripiprazole - SUBBAYAMMA, A.V.; RAMBABU, C. (Asian Journal of Chemistry, 2010)
A new spectrophotmetric method for the assay of trandolapril and aripiprazole has been described. The coloured species formed by interaction of cobalt thiocyanate and the experimental drugs. They form the coordination complex of the drug (electron donor) and the central metal atom of cobalt thiocyanate which is extractable into nitrobenzene from aqueous solution. The coloured complexes when trandolapril or aripiprazole is treated with cobalt thiocyanate due to the presence of secondary or tertiary amino group respectively, is the basis in the present investigation. It has maximum absorption at 620 nm. Beer's law limits, precision and accuracy of the methods are checked suitable for the assay of trandolapril and aripiprazole in the presence of other ingredients that are usually present in tablets.